Dosage Recommendation of Unbalanced Compound Fertilizers for Cabbage (Brassica oleracea) - Hafith Furqoni (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2026)
Fertilization serves as a fundamental component of crop cultivation, wherein the application of mineral nutrients is crucial for plant nourishment, facilitating various physiological processes critical for growth and development. The objective of this study is to establish an optimal recommended dosage that enhances cabbage growth and yield. The experimental design employed in this study was a randomized block design with four replications. The treatments consist of seven fertilization levels, as follows: No fertilization with nitrogen (N), phosphorus (P), or potassium (K) (P0), reference fertilization (P1), 0.5 dose of unbalanced compound fertilizers (P2), 0.75 dose of unbalanced compound fertilizers (P3), 1.0 dose of unbalanced compound fertilizers (P4), 1.25 dose of unbalanced compound fertilizers (P5), and 1.5 dose of unbalanced compound fertilizers (P6). The experiment indicated that the application of unbalanced compound fertilizers enhances cabbage plant growth, as evidenced by increased plant height and leaf number compared to the control treatment. Additionally, fertilization improves yield components relative to untreated plants. The application of 0.5 doses of unbalanced compound fertilizers proves agronomically effective, yielding the highest relative agronomic effectiveness at 169%, meaning a 1.69-fold increase in yield. Economically, the same dosage is also highly beneficial, achieving the highest R/C ratio of 2.35 and generating a profit of Rp. 14,365,150. The study results confirm that unbalanced compound fertilizers were both agronomically effective and economically advantageous. The recommended dosage for cabbage cultivation is 134 kg/ha, applied in two stages: 50% at 1 WAT (weeks after transplanting) and the remaining 50% at 4 WAT.